Recipient corneal thickness and visual outcome after Descemet's stripping automated endothelial keratoplasty. Issue 1 (16th October 2013) - Ivarsen, Anders; Hjortdal, Jesper
Abstract : Background: Descemet's stripping automated endothelial keratoplasty (DSAEK) is widely performed for endothelial failure. Unfortunately, the visual outcome is often mediocre and the underlying cause unclear. This study examines whether corneal light scatter and recipient corneal thickness (RCT) influence the visual outcome after DSAEK. Methods: Patients attending clinical control after DSAEK were recruited during 4 months. In total, 125 eyes from 93 patients were enrolled. Postoperative time averaged 20±13 months. Data from previous controls were also reviewed. Examinations included corrected distance visual acuity (CDVA), Pentacam and anterior-segment OCT. From OCT and Pentacam data, RCT and lamellar graft thickness (LGT) were determined. Corneal densitometry was estimated from Pentacam images. Results: 6 months after DSAEK, RCT measured 482±27 μm. After 3 years, RCT was significantly higher, measuring 505±23 μm. Pentacam and OCT showed similar variations in RCT. Also, in paired observations, from patients with previous controls, RCT increased significantly. Concurrently, corneal densitometry decreased and CDVA improved from 0.30±0.13 logMAR by 6 months to 0.17±0.08 logMAR by 4 years. No changes in LGT were observed. Changes in RCT, densitometry and CDVA were significantly correlated. Conclusions: The study suggests that changes in RCT and corneal densitometry are important for the visual outcome after DSAEK.